The effect of gamification in user satisfaction, the approval rate and academic performance - Martínez, Gabriela; Baldiris, Silvia; Salas, Daniel (Lecture Notes in Computer Science, 2020)
Continuous Education Centre from the National Polytechnic School of Ecuador (CEC-EPN) develops online education courses under a constructivist academic approach, following the ADDIE instructional approach, reaching more than 10,000 students per year. These courses implementation suffers common problems related to low student participation, low academic performance, low approval rate and low student satisfaction. The current trends of virtual education are influenced by new strategies such as the use of gamification in the design of virtual content; this is due to the good results it has had on motivation, academic performance and student participation. This document describes the implementation of a strategy of gamification based on role-play in a MOOC course on Prevention of Child Sexual Abuse in the CEC-EPN. The strategy was validated through an experimental design involving a control group (receiving a traditional course) and an experimental group (receiving the gamified course). The evaluation focuses on the analysis of the following variables: User Satisfaction, Approval Rate and Academic Performance. The results show the implemented strategy contributes to the improvement of the aforementioned variables.
Ponencia de la conferencia "4th International Symposium on Emerging Technologies for Education, SETE 2019, was held in conjunction with the 18th International Conference on Web-based Learning, ICWL 2019; Magdeburg; Germany; 23 September 2019 through 25 September 2019"
Keywords: gamification; MOOC courses; playful strategies; virtual education; Scopus(2)